2021
DOI: 10.3390/ijerph18178993
|View full text |Cite
|
Sign up to set email alerts
|

Open Issues in the Transition from NAFLD to MAFLD: The Experience of the Plinio Study

Abstract: Metabolic associated fatty liver diseases (MAFLD) definition was proposed to identify fatty liver condition associated to metabolic disorders and to replace non-alcoholic fatty liver disease (NAFLD). We aimed to explore the effect of the application of the new MAFLD criteria on a pre-existing cohort of NAFLD patients. The consequences of the reclassification were investigated by applying the MAFLD criteria to a prospective cohort (The Plinio Study) of dysmetabolic patients examined for the presence of NAFLD. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…However, many lines of evidence have proved that these patients might have metabolic dysfunction (e.g. : insulin resistance, diabetes, hypertension [55]) and, based on these cardio-metabolic risk profiles, might be included in the new MAFLD definition [56]. Not by chance, lean NAFLD patients have similar risk to develop cardiometabolic and liver complications as compared to obese ones [57].…”
Section: Nafld Geneticsmentioning
confidence: 99%
“…However, many lines of evidence have proved that these patients might have metabolic dysfunction (e.g. : insulin resistance, diabetes, hypertension [55]) and, based on these cardio-metabolic risk profiles, might be included in the new MAFLD definition [56]. Not by chance, lean NAFLD patients have similar risk to develop cardiometabolic and liver complications as compared to obese ones [57].…”
Section: Nafld Geneticsmentioning
confidence: 99%
“…When examining retrospective data comparing the two diagnoses, the majority of patients fulfill both the MAFLD and NAFLD criteria. However, there is a small proportion of patients who make up the non-MR NAFLD group across these studies, ranging from 0.6–16.1%, with most consistently estimating this group to make up around 5% of the fatty liver disease population [ 20 , 22 , 32 , 33 , 40 - 43 ]. While most risks were associated with MAFLD diagnosis, some studies did show that non-MR NAFLD patients had increased risks of cardiovascular disease during follow-up, though the majority of studies showed no increase in liver-related risk compared to the control populations [ 39 ].…”
Section: Mafld Vs Nafld – the Overall Benefitsmentioning
confidence: 99%
“…Hypercholesterolemia is characterized by elevated serum LDL‐C levels and a significantly increased risk of coronary heart disease (Baratta et al, 2023). Under physiological conditions, LDL‐C binds to the LDLR receptor on the surface of liver cells and enters the liver cells, while LDL‐C is degraded in the intracellular lysosome, and LDLR is recycled back to the cell membrane.…”
Section: Biological Functions Of Pcsk9mentioning
confidence: 99%
“…Hypercholesterolemia is an important cause of atherosclerosis, and lowering cholesterol is a preventive strategy. Low‐density lipoprotein cholesterol (LDL‐C) is the main driving factor for the formation, occurrence and development of atherosclerosis, which level is related to cardiovascular risk in a dose‐dependent manner (Baratta et al, 2023). Drugs targeting the regulation of LDL‐C, such as hydroxymethylglutaryl Coenzyme A (HMG‐CoA) reductase inhibitors and cholesterol absorption inhibitors, have been used clinically for many years, but their effectiveness is limited or some patients are intolerant (El Hussein et al, 2023).…”
Section: Introductionmentioning
confidence: 99%